Insight Islamophobia: Governing the public visibility of Islamic lifestyle in Turkey - NAS, ALPARSLAN; YEL, ALİ MURAT (SAGE PUBLICATIONS LTD, 2014)
This article engages in a critical discussion of the ways in which public visibility of the Islamic lifestyle is governed through the practices within visual culture in Turkey. It is possible to observe that in a society with a predominantly Muslim population, the media is dominated by the secularized imagery of everyday life, which is systematically abstracted from Islamic signifiers. Following a Foucauldian theoretical framework, this article shows that visual culture provides the necessary ground for the Kemalist modernization project to legitimize particular drives, which are inherently reproduced by a state of anxiety and fear against the Islamic lifestyle. Recent controversies the Turkish context show that Islamophobia should not solely be regarded as a phenomenon, which originated and still operates mainly in the West. Rather, the case of Turkey encourages one to critically negotiate the boundaries of visual culture, which is invested with particular strategies of power that reproduce the images of Islamic lifestyle as undesirable signifiers of culture.
Keywords: Conservatism; governmentality; Islamic lifestyle; Islamophobia; Kemalism; modernization; popular culture; secularism; Turkey; visual culture